CEO transformational leadership and top manager ambidexterity. Issue 8 (2nd November 2015) - Li, Ci-Rong; Lin, Chen-Ju; Tien, Yun-Hsiang
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the role of CEO transformational leadership in promoting ambidexterity of top managers. This paper posits that connecting CEO transformational leadership with the CEO-top manager interface offers a better explanation of heterogeneity in top manager ambidextrous behavior. Design/methodology/approach – This study is based on a questionnaire survey of 388 senior managers in 80 top teams nested in 80 small- to medium-sized Taiwan manufacturing firms. Findings – The findings indicate that transformational CEOs shape the CEO-top manager interface, characterized by senior team behavioral integration, decentralization of responsibilities, long-term compensation, and individual manager risk propensity, and in turn promote ambidexterity at the individual top manager level. Originality/value – Hence, the authors contribute to the existing understanding that transformational CEOs may not only have a beneficial influence on firm-level ambidexterity, but also may be particularly effective in enabling individual-level top managers to simultaneously explore and exploit.